Analyzing Advertising Acceptance through the Diffusion of Innovations Theory: An Investigation into CGI Advertising - ŞİŞMAN, ÖZGE ÖZKÖK (Erciyes Üniversitesi İletişim Fakültesi, 2025)
Adoption is considered a critical element in marketing communication, as it reflects the extent to which consumers accept an advertisement and its influence on purchase intent and brand preference. Perceived usefulness, perceived value, advertisement content, visual design, and message clarity are key factors shaping how consumers adopt and evaluate an advertisement. This study examines advertising acceptance within the Diffusion of Innovations Theory framework, focusing on CGI (Computer-Generated Imagery) advertising, which is increasingly adopted in digital advertising. The study explores the adoption process of CGI advertisements by analyzing the perspectives of industry professionals regarding this innovation. A qualitative research approach was employed, utilizing in-depth interviews with 15 experienced professionals from the advertising industry. The collected data were analyzed to assess the diffusion process of CGI advertisements, their perceived advantages, and the challenges encountered in the sector. The findings reveal how the acceptance of CGI advertising is shaped within the Diffusion of Innovations Theory, contributing to the theoretical framework in this field. The findings offer strategic recommendations to enhance CGI advertising and highlight the key role of user perspectives on visual creativity, usability, and message clarity in its adoption.
Keywords: Digital Advertising; Advertising Acceptance; CGI Advertising; Diffusion of Innovations Theory; Marketing Communication